The Development of Venture Capital Industry and Role of Government in Korea: Venture Boom vs. Post-Boom - Lee, Su Il (KDI 36th Anniversary International Conference: Financing Innovation-Oriented Business to Promote Entrepreneurship: Experiences of Advanced Countries and Lessons to Korea, 2007)
CHAPTER 5 / Suil Lee The Development of Venture Capital Industry and Role of Government in Korea: Venture Boom vs. Post-Boom 1. Introduction 2. Venture Capital Industry in Korea 3. Data 4. Fund-raising and the Role of Government 5. Investment and the Role of Government 6. Conclusion - Appendix